The Effect of Trimming and Sinkage on the Trimaran Resistance Calculation. (2015) - Deng, Rui; Li, Chao; Huang, Debo; Zhou, Guangli
Abstract: The clam water resistance as well as the resistance components of a trimaran test model with and without appendage is calculated by CFD method in the different conditions, taking viscous effect and the free surface into account, in order to investigate the effect of trimming and sinkage on the resistance calculation. The viscous flow field around the trimaran without appendage restrained and free in 6 degrees of freedom is simulated at different velocities, the numerical results of the free model are compared with the test data and show good agreement. The total resistance and the resistance of the main hull, as well as the outriggers are calculated and the details of the flow field are discussed. Then, the numerical results of the free model and the captive model are compared in order to analyse the effect of trimming and sinkage. The analysis of the comparison suggests that some of the resistance components are susceptible to the gesture. After that, the viscous flow field of the trimaran with T-foil is simulated and the total resistance, resistance components as well as the gesture are calculated. The comparison of the numerical results of the free model with T-foil and the experimental data also shows good agreement, and the details of viscous flow field as well as the resistance components are analyzed.